KOLABORASI GURU REGULER DAN GURU PENDAMPING KHUSUS DALAM PENGELOLAAN PERILAKU ABK MELALUI PENDEKATAN LOW AROUSAL - Maimuna, Septia; Fadilah, Yulina; Khosiah, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the collaborative strategies between regular teachers and Special Assistant Teachers (GPK) in managing the behavior of students with special needs (ABK) through the Low Arousal Approach in inclusive classrooms. A qualitative approach with a case study design was implemented at SD Muhammadiyah Plus, Probolinggo City, in December 2025. Data were collected through participatory observation, in-depth interviews, and document analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results indicate that Low Arousal principles such as calm communication, providing time out opportunities, environmental adjustments, and the use of a calming corner effectively reduced challenging behaviors such as tantrums, mild aggression, and anxiety. Collaboration between regular teachers and GPK played a key role in de-escalation and supported students’ self-regulation. The implementation of this strategy also fostered a more stable, empathetic, and conducive learning atmosphere for all students, while strengthening inclusive education practices in primary schools.